The Influence of Customer Care Service Management on the Performance of the Shops and Clothes Businesses in Bukoba Municipality in Tanzania - Rwehika, Irene; Magali, Joseph (Ushus Journal of Business Management, 2021)
This paper assessed the effects of customer care service management on business performance for the shop and clothes business owners in Bukoba municipality, Tanzania. Specifically, the paper assessed the effects of selling quality products, complaints management and positive impression on business performance. The study targeted a total population of 110 shop sellers and 850 customers. The systematic random sampling technique and sampling formula were used to select a sample size of 70 participants. The data were analyzed using descriptive statistics. The findings indicate that on average, shop sellers were selling products of the desired quality and this contributed to business performance. The findings further indicated that the positive impression was managed as required. However, the findings indicate that the impaired products replacement service was missing, the management for complaints was not sufficient, and shop sellers were busy and attended calls while serving customers. This, therefore, reduced business performance. This paper recommends that the business owners should accept replacing the impaired products, strive to make sure that all complaints are handled appropriately and timely and should refrain from being busy and attending calls when serving customers.